2011
DOI: 10.14411/eje.2011.044
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and pattern of expression of trehalose-6-phosphate synthase cDNA from Catantops pinguis (Orthoptera: Catantopidae)

Abstract: Abstract.Trehalose is not only an important disaccharide, but also a key stress resistance factor in the development of many organisms, including plants, bacteria, fungi, and insects. To study the potential function of trehalose in development and behaviour, cDNA for a trehalose-6-phosphate synthase from Catantops pinguis (CpiTPS) was cloned and sequenced. Results revealed that the CpiTPS cDNA sequence contains an open reading frame of 2430 nucleotides encoding a protein of 809 amino acids with a predicted mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…The first insect TPS gene was cloned in Drosophila (Chen et al, 2002 ; Chen and Haddad, 2004 ), and the induction of TPS1 gene expression was shown to increase tolerance to anoxia (Chen et al, 2002 ). Subsequently, insect TPS genes were cloned from Helicoverpa armigera (Xu et al, 2009 ), Locusta migratoria manilensis (Cui and Xia, 2009 ), Spodoptera exigua (Tang et al, 2010 ), Nilaparvata lugens (Chen et al, 2010b ), Catantops pinguis (Tang et al, 2011 ), Ctenocephalides felis (Kern et al, 2012 ), Harmonia axyridis (Qin et al, 2012 ), Blattella germanica (Chen and Zhang, 2015 ), Delia antiqua (Guo et al, 2015 ), Leptinotarsa decemlineata (Shi et al, 2016 ), Bactrocera minax (Xiong et al, 2016 ), and other organisms. Moreover, two TPS genes have been found in B. germanica, Tribolium castaneum , and Aphelenchoides besseyi , and three TPS genes have been found in Ascaris suum and N. lugens (Figure 1A and Table 1 , Shen, 2017 ).…”
Section: Genetic Architecturementioning
confidence: 99%
“…The first insect TPS gene was cloned in Drosophila (Chen et al, 2002 ; Chen and Haddad, 2004 ), and the induction of TPS1 gene expression was shown to increase tolerance to anoxia (Chen et al, 2002 ). Subsequently, insect TPS genes were cloned from Helicoverpa armigera (Xu et al, 2009 ), Locusta migratoria manilensis (Cui and Xia, 2009 ), Spodoptera exigua (Tang et al, 2010 ), Nilaparvata lugens (Chen et al, 2010b ), Catantops pinguis (Tang et al, 2011 ), Ctenocephalides felis (Kern et al, 2012 ), Harmonia axyridis (Qin et al, 2012 ), Blattella germanica (Chen and Zhang, 2015 ), Delia antiqua (Guo et al, 2015 ), Leptinotarsa decemlineata (Shi et al, 2016 ), Bactrocera minax (Xiong et al, 2016 ), and other organisms. Moreover, two TPS genes have been found in B. germanica, Tribolium castaneum , and Aphelenchoides besseyi , and three TPS genes have been found in Ascaris suum and N. lugens (Figure 1A and Table 1 , Shen, 2017 ).…”
Section: Genetic Architecturementioning
confidence: 99%
“…The TPS gene in insects was first reported in Drosophila melanogaster [32]. To date, many TPS genes have been reported from several insects, including Heortia vitessoides (Lepidoptera: Crambidae) [20], Locusta migratoria manilensis (Orthoptera: Acrididae) [33], Tribolium castaneum (Coleoptera: Tenebrionidae) [22], Spodoptera exigua (Lepidoptera: Noctuidae) [34], the brown planthopper, Nilaparvata lugens Stål (Hemiptera: Delphacidae) [24] and Catantops pinguis (Orthoptera: Catantopidae) [35]. However, the TPS mode of functionality has not been reported in D. citri.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first insect TPS gene was discovered and cloned in the fruit fly Drosophila melanogaster in 2002 (Chen et al , 2002), many TPS homologs have been cloned and reported from a variety of insects, including the cotton bollworm ( Helicoverpa armigera ) (Xu et al , 2009), the brown planthopper ( Nilaparvata lugens , Stål) (Chen et al , 2010 b ; Yang et al , 2017), the beet armyworm ( Spodoptera exigua Hübner) (Tang et al , 2010), the locust ( Catantops pinguis Stål) (Tang et al , 2011), the German cockroach ( Blattella germanica Linnaeus) (Chen & Zhang, 2015), the Chinese citrus fly ( Bactrocera minax Enderlein) (Xiong et al , 2016), and the Colorado potato beetle ( Leptinotarsa decemlineata Say) (Shi et al , 2016). Moreover, two TPS genes in B. germanica ( BgTPS 1: KR050213 and BgTPS 2: KR050214) and in N. lugens ( NlTPS1 : GQ397450 and NlTPS2 : KU556826) have been cloned (Chen & Zhang, 2015; Yang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%